Performance evaluation of Fly ash based GPC with partial replacement of RHA as a cementitious material. (2020) - Parthiban, D.; Vijayan, D.S.; Sanjay Kumar, R.; Santhu, Anandhu P.; Abraham Cherian, Glenson; Ashiq, Mohammed
Abstract: The evaluation of geopolymer concrete means that does not utilize cement in its manufacturing, it can be seen as an important achievement in this context. This experimental investigation shows that the experimental tests are carried out on fly ash and Rice husk ash-based GPC. Geopolymer solutions are prepared to make an alkaline medium based on sodium compounds. The molarity value was fixed at 8 to prepare the sodium-based hydroxide solution and the alkaline ratio between sodium-based silicate to sodium-based hydroxide was fixed as 2.5 to prepare an alkaline solution. The effects over the substitutes of FA with RHA were studied by conducting the compressive test, split tensile test and Stress–strain behavior of cylinder with and without confinement were studied at the ages of 7, 14, and 28 days curing respectively. Test results of workability in fresh concrete and GPC mixes indicate that in the fresh state were cohesive and stiffness with a medium degree of workability slump value of 73 mm is obtained. The study concludes that the replacement of FA with RHA in various proportions is not shown any positive result when compared to conventional concrete, Hence the usage of RHA with GPC shouldn't be prescribed one.